2018
DOI: 10.1002/jcb.26675
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR‐203 in estrogen receptor‐mediated signaling in the rat uterus and endometrial carcinoma

Abstract: The role of microRNAs (miRNA) in estrogen receptor (ER) signaling in the uterus and in endometrial cancer is not well understood. We therefore analyzed miRNA expression in uterine samples from a standard 3-day uterotrophic assay using young female adult rats to identify E2-regulated miRNAs. Microarray analysis identified 47 E2 down-regulated miRNAs including miR-30a, and 25 E2up-regulated miRNAs including miR-672, miR-203, and miR-146b. The strongly E2-upregulated miR-203 was selected for further analysis. miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Thereby, the protective effect of rs1536309 might be more easily observed in older patients. In a recent study, the upregulated miR-146b-5p was found correlated with E2 expression (20). Thus, the influence of this SNP site might be attenuated in female due to the higher level of miR-146b-5p.…”
Section: Discussionmentioning
confidence: 90%
“…Thereby, the protective effect of rs1536309 might be more easily observed in older patients. In a recent study, the upregulated miR-146b-5p was found correlated with E2 expression (20). Thus, the influence of this SNP site might be attenuated in female due to the higher level of miR-146b-5p.…”
Section: Discussionmentioning
confidence: 90%
“…The two networks closely communicating each other by sharing a few common genes. For example, NFAT5 is regulated by an estrogen-induced microRNA [37] and the regulation is mediated via PI3K/AKT-signaling pathways [38]. In addition, A100A9, a calcium-binding protein that is highly expressed in malignant breast cancer, induces a decrease of ERα in MCF-7 cell [35], and inhibits PI3K/AKT pathway in pancreatic adenocarcinoma cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Pathological changes in these genes can cause anomalistic transduction of signal pathways such as AKT‐/‐PI3K, NF‐κB, MARK, and Wnt‐/‐β‐catenin, or abnormal expression of P53 and P16 proteins, leading to uncontrolled cell proliferation and tumorigenesis. Given its extensive study in tumors and obvious therapeutic effect, the CRISPR‐Cas9 technology has been used in related research and treatment of endometrial cancer (summarized in Table ).…”
Section: Endometrial Cancer and Crispr‐cas9mentioning
confidence: 99%
“…SDPR gene depletion by CRISPR‐Cas9 in HEC‐1B and HEC‐108 cells can suppress tumor cell migration, invasion and EMT by inhibiting the ILK‐/‐ALDH1 pathway . Knockout of MIR‐203 in RUCA‐1 cells caused tumor cells to stagnate in the G2 phase of the cell cycle and cell viability also decreased . In short, because endometrial cancer is a multigene regulatory disease, many specific mechanisms are still unclear.…”
Section: Endometrial Cancer and Crispr‐cas9mentioning
confidence: 99%